Surface deformation relief as an indicator of fatigue damage under two-step loading sequences - Karuskevych, M.; Maslak, T.; Karuskevych, O.; Korchuk, V. (Problems of Tribology, 2026)
The study investigates the possibility of predicting the residual fatigue life of clad structural aluminum alloys based on the quantitative evaluation of surface deformation relief formed during cyclic loading. Fatigue damage accumulation in metallic structures is accompanied by microstructural transformations caused by dislocation motion along crystallographic planes. These processes lead to the formation of characteristic surface features such as slip bands, extrusions, and intrusions. Although these structures are three-dimensional, their development can be effectively assessed using two-dimensional optical microscopy images, enabling quantitative analysis of the deformation relief evolution during fatigue loading. The research focuses on clad aluminum alloys widely used in aircraft structures, including D16ATV, V95, 2024-T3, and 7075-T6. The obtained data allowed regression models to be developed that relate the damage parameter to the relative residual fatigue life. The proposed approach was extended from regular cyclic loading to simple irregular loading regimes, specifically two-step loading sequences of the “low–high” and “high–low” types. The results were compared with predictions based on Miner’s linear fatigue damage summation rule. Within a certain range of cyclic stresses, the developed regression model provides prediction accuracy comparable to, and in some cases exceeding, that obtained using Miner’s rule. The results confirm that the saturation of surface deformation relief can serve as a structurally sensitive indicator of accumulated fatigue damage. The proposed methodology can be applied both to direct monitoring of clad aluminum structural components and to the fatigue indicators for metal structures of aircraft, bridge, pressure vessels